Improved models incorporating gender impacts in Livestock Master Plans - CGIAR Research Program on Livestock (2021)
A literature review and a round of expert consultations have been completed that help define a conceptual framework for incorporating gender in the economic modeling for Livestock Master Plans (LMPs). We have identified an appropriate analytical method and model specifications to implement the modeling of gender dynamics for LMPs.